Designing Buyback Contracts for Irrational But Predictable Newsvendors - Becker-Peth, Michael; Katok, Elena; Thonemann, Ulrich W. (Management Science, 2013)
One of the main assumptions in research on designing supply contracts is that decision makers act in a way that maximizes their expected profit. A number of laboratory experiments demonstrate that this assumption does not hold. Specifically, faced with uncertain demand, decision makers place orders that systematically deviate from the expected profit maximizing levels. We have added to this body of knowledge by demonstrating that ordering decisions also systematically depend on individual contract parameters and by developing a behavioral model that captures this systematic behavior. We proceed to test our behavioral model using laboratory experiments and use the data to derive empirical model parameters. We then test our approach in out-of-sample validation experiments that confirm that, indeed, contracts designed using the behavioral model perform better than contracts designed using the standard model. This paper was accepted by Christian Terwiesch, operations management.